Cloning and functional analysis of mitogen‐activated protein kinases 6 gene in lettuce. (12th April 2022) - Wang, Tingzhen; Liu, Mingjia; Tian, Yufeng; Han, Yingyan; Liu, Chaojie; Hao, Jinghong; Fan, Shuangxi
Abstract: Lettuce ( Lactuca sativa L.) being a cool‐season crop can bolt if the temperatures increase above 20 °C. When lettuce bolts, the plants start the reproductive growth cycle. The improvement in resistance to high temperature bolting has been an important goal of lettuce breeding. This paper verified that Lactuca sativa mitogen‐activated protein kinases 6 ( LsMAPK6 ) played an important role in high temperature bolting. The full‐length CDS of LsMAPK6 gene was amplified by real‐time polymerase chain reaction (RT‐PCR) and analyzed by bioinformatics software. The expression of LsMAPK6 was determined by quantitative real‐time polymerase chain reaction (qRT‐PCR). The results showed that the length of LsMAPK6 was 1, 182 bp, encoding 393 amino acids. The protein domain was STKc_TEY_MAPK and closely relevant to sunflower ( Helianthus annuus L.), mouse‐ear cress [ Arabidopsis thaliana (L.) Heynh.], and chrysanthemum ( Chrysanthemum morifolium Ramat.). The qRT‐PCR showed that Lsmapk6 was mainly expressed in stem, stem apex, and taproot, and high temperature significantly promoted its expression. Virus‐induced gene silencing (VIGS) technology successfully silenced LsMAPK6 in lettuce, and the bolting of silenced lines was delayed under the action of high temperature and exogenous gibberellin. These suggest that LsMAPK6 plays an important role in promoting bolting. This study laid a foundation for further study on the function and regulation mechanism of MAPK6. Core Ideas: This analysis lays the foundation for further research on vegetable bolting at high temperature. LsMAPK6 gene was successfully cloned. The characteristics of LsMAPK6 were learned by various bioinformatics analyses. High temperature positively regulates the expression of LsMAPK6 in lettuce. Virus‐induced gene silencing of LsMAPK6 inhibited bolting of lettuce.